2008
DOI: 10.1007/s10290-008-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Changes in Product Quality in Marginal Intra-Industry Trade

Abstract: Intra-industry trade, adjustment costs, quality, product differentiation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, this study has some limitations. The study needs to research on vertical and horizontal MIIT because it can be shown the two-way trade of different endowments and quality products [17]. On the other hand, the study will use a different method to estimate labor cost such as the method proposed by [18,19] to solve some econometric problems such as endogeneity of some explanatory variable.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study has some limitations. The study needs to research on vertical and horizontal MIIT because it can be shown the two-way trade of different endowments and quality products [17]. On the other hand, the study will use a different method to estimate labor cost such as the method proposed by [18,19] to solve some econometric problems such as endogeneity of some explanatory variable.…”
Section: Resultsmentioning
confidence: 99%
“…(2008) and Wang (2014). Some believe that there are flaws in measuring product quality simply by using price and also take into consideration the inputs and the costs of the materials used in the production process (Azhar and Elliott, 2008; Eshraghi and Ismail, 2013). Even with this additional research, there is still a view that the quality of a country's exports cannot be determined using the price and cost of inputs, and that quality is differentiated from the perspective of exporters and importers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Brülhart and Elliott (2002), Brülhart et al (2006) and Cabral and Silva (2006) proposed empirical tests of the smooth-adjustment hypothesis (SAH) associated with MIIT. To discuss the SAH, a conventional decomposition into HIIT and VIIT is appropriate (Greenaway et al, 2002;Brülhart and Elliott, 2002;Azhar and Elliott, 2008a). According to the SAH, the adjustment costs associated with inter-industry trade are higher than those associated with IIT because a change in the former generally requires greater resource reallocation.…”
Section: Beyond Ghmmentioning
confidence: 99%